HUMAN RIGHTS AND A PERSON’S NAME: LEGAL TRENDS AND CHALLENGES - de Varennes, Dr Fernand (Teisė, 2015)
This article explains the recent evolution in the recognition and use of a person‘s own name in international human rights. It examines the historical reasons why this central aspect of individual identity was initially largely omitted from earlier treaties because of the different traditions on whether individuals could freely assert their identity through the use of their own name and surname, particularly in Europe where common law and civil approaches on the matter were significantly different. It shows how there has been significant changes in recent jurisprudence internationally and in Europe that have focused increasingly on the importance of an individual’s identity, and that this means vulnerable segments of society such as children, women and minorities must generally be entitled to have their own names recognised and used by state authorities, rather than having authorities impose an officially acceptable version.